2010
DOI: 10.1108/14714171011083579
|View full text |Cite
|
Sign up to set email alerts
|

Understanding construction competitiveness: the contribution of system dynamics

Abstract: PurposeConstruction sector competitiveness has been a subject of interest for many years.Research too often focuses on the means of overcoming the 'barriers to change' as if such barriers were static entities. There has been little attempt to understand the dynamic interrelationship between the differing factors which impinge upon construction sector competitiveness. The paper outlines the benefits of taking a systems approach to construction competitiveness research. Design/methodology/approachThe System Dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 20 publications
(26 reference statements)
1
25
0
2
Order By: Relevance
“…The idea is that 'small but significant' change can in the long-term, be the most effective method of implementing industry-wide change. In addition, focusing on individual projects, the unit of industry production (Kenley 2014) is also an obvious fit-for-purpose as a way of changing industry practice (Dangerfield, Green & Austin 2010).…”
Section: Lessons Learned: Be Incremental Not Aspirationalmentioning
confidence: 99%
See 4 more Smart Citations
“…The idea is that 'small but significant' change can in the long-term, be the most effective method of implementing industry-wide change. In addition, focusing on individual projects, the unit of industry production (Kenley 2014) is also an obvious fit-for-purpose as a way of changing industry practice (Dangerfield, Green & Austin 2010).…”
Section: Lessons Learned: Be Incremental Not Aspirationalmentioning
confidence: 99%
“…Given that equipment schematics all held similar graphic artefacts, it was assumed that a single standard project could identify the information-based transformation of those drawings, even though each specification is based on only the relevant geometric information. Could this be an example of the two universal limiting factors; the optimistic human tendency and the need to sell impossible project outcomes (Dangerfield, Green & Austin 2010)? However, a systematic review of the problem by the ICT project team, with the input of end-users, found that the underlying knowledge represented in the three major building service systems (temperature control, electrical power, and water) were very different. Thus, the expected single project, of necessity, became three discipline-specific specification projects.…”
Section: Lessons Learned: Be Specific Not Abstractmentioning
confidence: 99%
See 3 more Smart Citations